DAMPAK KONVERSI LAHAN TERHADAP KECUKUPAN DAN KETAHANAN PANGAN DI PROVINSI RIAU - Rachmiwati Yusuf; Indra Fuadi (DINAMIKA PERTANIAN, 2014)
This study of the effect of food land conversion on non food toward the adequate and resistance of food was carried out in the year of 2010. The location was Indragiri Hilir and Kampar regencies because the two regencies are the cebter of food plant production, especially rice crop amd other food crops in Riau Province. The financial analysis of food plant agriculture, especially rice field and soybean or non food (rubber, coconut and oil palm) showed that they were beneficial farming in agriculture. However, most of the existing food plant farmers had changed their business into plantation cutivation, especially oil palm and remain only 0.25 ha for food crop with production only for family needs (subsistence). The land conversion was carried out because te pantation had many benefits. Land field is rentet by plantation Entrepreneur. The owner can work in his or her field as worker and get the harvest with certain percentage according to the agreed agreement. The effect of the change of land funtion in Riau Province annually caused a lack of rice at arrange of 200.000-300.000 ton/year.